2004
DOI: 10.1590/s0066-782x2004001000004
|View full text |Cite
|
Sign up to set email alerts
|

IV Diretrizes Brasileiras de Hipertensão Arterial

Abstract: Realização Work performed by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 21 publications
0
2
0
3
Order By: Relevance
“…48 Previous studies showed that treatment with enalapril did not improve the serum and urinary levels of creatinine, 43 which corroborates with the results shown in this study. In patients with renovascular hypertension, the treatment with enalapril may cause reduced glomerular filtration that increases creatinine levels; however, in the long term, its nephroprotective effects prevail, 49 which explains the treatment with enalapril not having improved creatinine levels. We demonstrated that ASE treatment improved renal function parameters evidenced by restoration of serum and urinary levels of creatinine and urea, urinary volume, and proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…48 Previous studies showed that treatment with enalapril did not improve the serum and urinary levels of creatinine, 43 which corroborates with the results shown in this study. In patients with renovascular hypertension, the treatment with enalapril may cause reduced glomerular filtration that increases creatinine levels; however, in the long term, its nephroprotective effects prevail, 49 which explains the treatment with enalapril not having improved creatinine levels. We demonstrated that ASE treatment improved renal function parameters evidenced by restoration of serum and urinary levels of creatinine and urea, urinary volume, and proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…The disease was considered active when IGF-1 was above the normal value for age and gender, even when using cabergoline, octreotide, or pegvisomant; considered controlled when the use of these drugs kept blood concentrations of IGF-1 within the normal range; and considered cured when the concentrations of this hormone were within the normal range without the use of these drugs. Hypertensive participants were considered as those with blood pressure equal to or >140 × 90 mmHg, or those using anti-hypertensive drugs (25). A participant was considered to have diabetes mellitus type 2 when glycemia was equal to or higher than 125 mg/dL, or 2 h post oral glucose tolerance test higher than 199 mg/dL or HbA1 levels equal to or higher 6.5%, or if he/she was using hypoglycemic drugs (26).…”
Section: Methodsmentioning
confidence: 99%
“…inadequada, que pode agravar o quadro clínico. A não compreensão da terapia prescrita pode ser uma das razões pelas quais medicamentos reconhecidamente eficazes sob condições controladas, se tornam inefetivos quando utilizados na prática clínica habitual (29).…”
Section: Classificaçãounclassified